Analysis of Media and Learning Resources Used by Teachers in the Topic of Direct Current Circuits in Physics - Nurhamdin Putra; Iskandar Zulkarnain; Wandika Wandika; Desnita Desnita; Usmeldi Usmeldi (Jurnal Ilmiah Pendidikan Fisika, 2024)
This study aims to analyze the media and learning resources used in 6 public and private high schools to explain the 12th-grade Physics material of Direct Current (DC) circuits and to analyze the media and learning resources with the potential for development in teaching Physics, particularly in the topic of DC circuits, in these six schools. The research employed a quantitative descriptive method with a survey approach, and the instrument used was a questionnaire. The data were obtained from the distribution of questionnaires, with 282 respondents from 6 different schools. The collected data were analyzed by calculating the percentage of media and learning resources used by the six schools. The results showed that the learning media with the highest percentage is "other media," including print media (textbooks), whiteboards, and direct explanations by teachers, with 40.46%. Meanwhile, the lowest percentage is for PhET at 10.54%. Regarding learning resources, printed books have the highest percentage at 44.98% and the lowest for modules at 9.17%. In conclusion, the most widely used media by the six schools to explain DC circuits are print media (textbooks), whiteboards, and direct explanations by teachers. The most commonly used learning resource is printed books. Additionally, the media with the potential for development is PhET, and the learning resource with development potential is modules. This is because these media and learning resources are still underutilized in the six public and private high schools when explaining DC circuits. This research provides insights into the needed media and learning resources, their limited availability, and their potential for development in teaching DC circuits in these six public and private high schools.